Development Of Interactive Learning Media Based On Open Technology - Nurul Aisyah Binti Ahmad; Budi Santoso (CV JK Riset Publishing Group, 2025)
This study aims to develop interactive learning media based on open-source technology to enhance the quality of education in secondary schools. The background of this research arises from the need for innovative media that is not only visually appealing but also capable of fostering active student engagement. The research employed a Research and Development (R&D) approach with a modified Borg & Gall model, including preliminary studies, product design, expert validation, limited trials, revisions, and field testing. The findings indicate that open-source interactive media can increase learning motivation, strengthen conceptual understanding, and provide teachers with creative flexibility in adapting learning content. However, challenges such as limited digital literacy among teachers and infrastructure gaps remain significant barriers to implementation in resource-limited schools. Therefore, systematic training, stakeholder collaboration, and infrastructure support are essential for sustainable utilization of interactive media. This study concludes that open-source technology holds strong potential as a strategic instrument for educational equity and quality improvement in Indonesia.